Ischemia increases cortical Na+,K+-ATPase activity (K-Pase) in a model of kidney auto-transplantation in the large white pig - Fares, M.; François, C.; Maixent, J. M. (Cellular and Molecular Biology, 2014)
Acute renal failure (ARF) induced by Ischemia-Reperfusion (I-R) is associated with a significant impairment of tubular sodium reabsorption. Na+,K+-ATPase has a crucial role in tubular sodium reabsorption and maintenance of water and ion homeostasis. In this study, we examined whether renal I-R affects Na+,K+-ATPase activity in a renal auto graft model (Large White Pig) with controlateral nephrectomy. Kidney samples were obtained from medulla (n = 4) and cortex (n = 3) after one hour of warm ischemia in autotransplanted models. These experimental groups were compared with a controlateral nephrectomy group (Control). Na+,K+-ATPase activity in purified membrane fractions was measured as ouabain-sensitive K+ -stimulated paranitrophenyl phosphatase (pNPPase) activity. The Na+,K+-ATPase activities of control, ischemia and ischemia –reperfusion were significantly higher in the medulla than in the cortex, irrespective of the experimental group (P<0.05). In cortices, Na+,K+-ATPase activity increased significantly (P<0.05) by 35% after ischemia compared to control group. In medullae, there was only a trend toward an activation of Na+,K+-ATPase activity after Ischemia (increased by 25%) and after Ischemia-Reperfusion (increased by 30%) compared to control group, and these differences did not reach statistical significance. These data suggest that renal ischemia induces a significant alteration of Na+,K+-ATPase by increasing its ouabain-sensitive K+-stimulated paranitrophenyl phosphatase (pNPPase) activity in isolated membrane from cortical renal tissues after one hour of ischemia. This change of activity seems to be a new regulation mechanism of an important membrane ion transporter during renal I-R in the large pig model of renal transplantation.